2010
DOI: 10.1093/humupd/dmq032
|View full text |Cite
|
Sign up to set email alerts
|

Extra- and intra-ovarian factors in polycystic ovary syndrome: impact on oocyte maturation and embryo developmental competence

Abstract: BACKGROUNDPolycystic ovary syndrome (PCOS) is a common metabolic dysfunction and heterogeneous endocrine disorder in women of reproductive age. Although patients with PCOS are typically characterized by increased numbers of oocytes retrieved during IVF, they are often of poor quality, leading to lower fertilization, cleavage and implantation rates, and a higher miscarriage rate.METHODSFor this review, we searched the database MEDLINE (1950 to January 2010) and Google for all full texts and/or abstract articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
314
3
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 396 publications
(353 citation statements)
references
References 277 publications
11
314
3
5
Order By: Relevance
“…It was suggested that this increased miscarriage rate in PCOS was not explained genetically by increased risk of embryonic aneuploidy [21]. As reviewed by Qiao and Feng [22], there is a multitude of endocrine and metabolic dysfunctions like LH hypersecretion, hyperandrogenaemia and hyperinsulinaemia, as well as altered intraovarian paracrine/autocrine factors, which are characteristic of PCOS and could be implicated in the impaired embryo developmental competence observed in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that this increased miscarriage rate in PCOS was not explained genetically by increased risk of embryonic aneuploidy [21]. As reviewed by Qiao and Feng [22], there is a multitude of endocrine and metabolic dysfunctions like LH hypersecretion, hyperandrogenaemia and hyperinsulinaemia, as well as altered intraovarian paracrine/autocrine factors, which are characteristic of PCOS and could be implicated in the impaired embryo developmental competence observed in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the inhibition of the expression of some proteins required for oocyte growth, for example the differentiating growth factor (GDF-9). Other authors (9,27) have shown that in the case of women who suffer from PCOS resulting from hyperandrogenism, the expression of this protein is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have reported that there are abnormalities in the transcription of certain genes in oocytes obtained from women with PCOS (7,27). It has been shown that T has an effect on the expression of proteins from the family of transforming growth factor beta (TGF-β), for example there is a lower level of GDF-9 transcript in oocytes isolated from women with PCOS (27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations